2015
DOI: 10.1080/00405000.2014.1000014
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of cotton wax removal using bacteria isolate from gin trash

Abstract: This study was conducted to establish optimal temperature, pH and incubation time for bacteria from gin trash, for enhancing wax removal during cotton bioscouring. Universal Rotatable Experimental Design was used for the process of optimisation and efficiency assessed by the percentage weight loss after solvent extraction of the treated fibres. Optimum wax of 0.765% out of 1.2% present in the fibres was removed at 45°C, pH 8 within 1 h. Minitab 15 and Monte Carlos were used for the parameter modelling and sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…According to Klapper et al (2002), hydroxyl and carboxylate groups of polysaccharides impart good adhesion to surfaces and form strong cohesive strength. The change could also be associated to the stiffer feel of the bacteria broth treated fibres reported in Mburu et al (2015a).…”
Section: Influence Of Bacteria Treatment On Cotton Fibre Propertiesmentioning
confidence: 85%
See 1 more Smart Citation
“…According to Klapper et al (2002), hydroxyl and carboxylate groups of polysaccharides impart good adhesion to surfaces and form strong cohesive strength. The change could also be associated to the stiffer feel of the bacteria broth treated fibres reported in Mburu et al (2015a).…”
Section: Influence Of Bacteria Treatment On Cotton Fibre Propertiesmentioning
confidence: 85%
“…Incorporating 5% of bacterial cellulose with wood pulp during paper sheet formation was found to significantly improve kaolin retention, strength and fire resistance as compared to plain paper sheets (Torres et al, 2012). Mburu et al (2015aMburu et al ( , 2015b reported that gram-positive streptobacilli isolated from RJTA 24,3 gin trash soil had activity on cotton fibre wax. Besides degrading 0.765% out of the 1.2% wax present, the treated fibres were found to exhibit a stiffer feel compared to the untreated fibres.…”
Section: Introductionmentioning
confidence: 99%